Evaluation Of Coronary Heart Disease Risk Among Patients With Type 2 Diabetes In Hospital Pulau Pinang, Malaysia - Majeed, Saif Aldin R. Abdul (2011)
The prevalence of diabetes mellitus had increased tremendously in the Malaysian population during the last decade. In addition to that, cardiovascular disease (CVD) reported to be an important cause of morbidity and mortality in Malaysia. Patients with diabetes are more likely to develop coronary heart disease (CHD) than a non diabetic population. Moreover, patients with diabetes but without clinical evidence of CHD own the same risk for CHD events as patients without diabetes but with CHD. The classical risk factors for CHD play an important role in the CHD risk estimation among patients with diabetes. These risk factors are age, gender, smoking status, hyperglycaemia, hypertension, dyslipidaemia and obesity.